37.2dB small-signal gain from Er/Yb Co-doped fiber amplifier with 20mW pump power - Harun, Sulaiman Wadi; Abdul Rashid, Hairul Azhar; Muhd-Yassin, S. Z.; Abd-Rahman, M. K.; Jayapalan, K. K.; Ahmad, Harith (ELSEVIER SCI LTD, 2008)
An efficient erbium-ytterbium-doped fiber amplifier (EYDFA) is demonstrated by forward and backward pumping a 3 in erbium/ytterbium co-doped fibers (EYDF) in single- and double-pass configurations using a 20 mW pump. At the input signal wavelength of 1536nm, the forward- and backward-pumped double-pass amplifiers achieved a maximum low-signal gain of 37.2 and 28.6dB and a corresponding noise figure of 5.4 and 10.8 dB, respectively. Whereas, the forward- and backward-pumped single-pass amplifiers (at the same wavelength) achieved a maximum low-signal gain of 20.0 and 22.2dB and a corresponding noise figure of 4.6 and 10.3dB, respectively. The double-pass design offers an economical solution to high-efficiency and high-gain optical amplifiers. (c) 2007 Elsevier Ltd. All rights reserved.